Structural behavior of damaged reinforced concrete beams under static cyclic loading (Fracture and Structural Integrity, 2022)
Bridges are regarded as one of the most important components of transportation infrastructure. More and more repairs, inspections, alterations, and construction processes are required to maintain safe usage due to increasing travel demands in addition to bridge infrastructure aging. In this paper, we will discuss the experimental investigation using five reinforced concrete beams to evaluate the effect of making damage to experimental beams under static cyclic loading to investigate their ductility and energy dissipation. The defective parameters taken into consideration in the experimental program were the gap in the concrete mold and mild steel at the middle bottom reinforcement. All tested specimens had the same cross-sectional dimensions. The concrete dimensions of the beams were 200 mm in width and 300 mm in height, and the beam's length was selected to be 2200 mm, having a clear span of 2000 mm between the supports, they were tested in positive bending using a 3-point bending load system. According to the results, when (RC) beams were subjected to any of the mentioned types of damage, they showed a significant decrease in ultimate capacities ranging from 3.03% to 19.31%. The ANSYS model shows an average difference with the experimental program within 4 % as an acceptable agreement.
Keywords: Monitoring; Cyclic loading; Damage Detection; Ductility; ANSYS